Robot-assisted aquablation for resection of benign prostatic hyperplasia: A series of cases - Eduardo García-Cruz; Javier Romero Otero; Pilar Altés Ineva; Luís Miguel Marco Pérez; Llorenç Pinsach Elías; Antonio Alcaraz Asensio (Journal of Clinical and Investigative Surgery, 2020)
Objective. The objective of this study was to assess the surgical outcomes of aquablation for treatment of benign prostatic hyperplasia, especially on ejaculatory function and urinary continence. Materials and Methods. A retrospective analysis was conducted, on patients >40 years, with lower urinary tract symptoms secondary to benign prostatic hyperplasia, and a prostate volume 60% score reduction without losing their ejaculatory function and urinary continence. No serious adverse events were reported. Conclusions. In our experience, aquablation is an efficient and safe method that offers high cut precision for prostate resection.